Manufatura aditiva por fusão de leito de pó a laser de aço inoxidável 316L com adições de boro: avaliação das propriedades de corrosão e desgaste - Figueira, Gustavo (2024)
Adding boron to stainless steels improves wear resistance through the formation of Cr- and Mo-rich borides but may cause sensitization. Enhancing wear without compromising corrosion resistance requires adjusting the alloy’s global composition. This thesis aims to modify 316L stainless steel, known for excellent processability by laser additive manufacturing, and evaluate its electrochemical and tribological properties after gas atomization and L-PBF. Initial tests with commercial 316L powder achieved high densification (8.09 ± 0.04 g/cm³) using parameters of 192 W, 1000 mm/s, 70 µm, and 30 µm. The composition was then modified with 0.5 wt.% B, designing two alloys (Mo3 and Mo4) via CALPHAD. Ingots were produced, gas-atomized, and characterized by SEM, XRD, and laser diffraction, revealing spherical powders suitable for L-PBF. A Box-Behnken design defined parameters for modified alloys (224 W, 700 mm/s, 76 µm). Specimens were printed and analyzed by SEM, TEM, and XRD, confirming a cellular microstructure with M₂B and M₃B₂ boride networks. Electrochemical tests showed superior performance of modified alloys compared to original 316L, with higher Etransp and Rp and lower icorr, ipass, Ceff, and Qa. Regarding wear, hardness increased from 224 ± 7 HV to 473 ± 5 HV, while the coefficient of friction dropped from 0.56 to 0.35, reducing the specific wear rate by up to 2.5 times. In conclusion, boron addition combined with composition adjustment significantly improved wear resistance without impairing corrosion resistance, maintaining L-PBF processability.